RELIGIOUS MODERATION IN THE PERSPECTIVE OF MILLENNIAL STUDENTS IN ISLAMIC BOARDING SCHOOLS - Maula Abdul Affuw Mandat; Muhammad Wildan Shohib (PAI RAFAH, 2023)
This study aims to analyze how religious moderation is implemented at the Hidayatullah Islamic boarding school in Yogyakarta and the role of millennial students at the Hidayatullah Yogyakarta Islamic boarding school in realizing religious moderation. The research method used is descriptive-qualitative, which allows researchers to explore the understanding and meaning behind the development of religious moderation at the Hidayatullah Islamic Boarding School, Yogyakarta. Data was collected through interviews and direct observation at the Islamic boarding school. Research findings show that the Hidayatullah Islamic Boarding School implements religious moderation with the principle of "Tawasuth" as the main foundation, maintaining balance and preventing extremism among students. The principles of “Tawazun,” “Tasamuh,” and “Al-Adil” are implemented through various activities, creating an educational environment that supports moderation and avoids extremism. The role of millennial students at the Hidayatullah Islamic Boarding School is necessary, and they use technology to spread religious education, become mediators in religious dialogue, and socialize the values of moderation. Their creativity and humanitarian spirit help bridge the gap between religious traditions and the modern world. In this way, the Hidayatullah Islamic Boarding School becomes a place where religious moderation can develop and be realized